Spatial perception and spatial experience in 3D worlds - Weigelt, K. (International Journal of Computer Science in Sport, 2012)
In 3D worlds, the added dimension gives users the feeling of perceiving a more realistic presentation. Therefore, 3D is very attractive for different research and development areas like in the field of Games and Serious Games. The spatial perception and spatial presence experience of the user are different when using 3D in contrast to 2D applications. In the context of the project `Sports in three dimensional television - Effects on spatial perception and spatial experience` the quantitative mechanisms of depth perception and the qualitative experience of spatial presence are discussed. The differences of 2D and 3D sport presentations and scenic presentations within one (and between different) sport discipline(s) are studied in detail in the context of a multilevel analysis. The purpose of this paper is to introduce first the theoretical framework of the project and second the empirical approach. As the project is in an early stage only few results of conducted qualitative interviews are presented. Transfer effects from 3DTV to the Game Industry are outlined, such as useful aspects which can enhance the 3D effect.